Early pharmacological profiling of isatin derivatives as potent and selective cytotoxic agents - Puerta, Adrián; González-Bakker, Aday; Brandão, Pedro; Pineiro, Marta; Burke, Anthony J.; Giovannetti, Elisa; Fernandes, Miguel X.; Padrón, José M. (Biochemical pharmacology, 2024)
[Display omitted] Isatin derivatives have attracted a lot of interest for their potential in the development of new anticancer drugs. A library of 38 isatin derivatives, created through an Ugi four-component reaction, underwent an initial screening in a panel of six human solid tumor cell lines. The four most active derivatives were then selected for further testing. These compounds showed selectivity towards the non-small cell lung cancer (NSCLC) cell line SW1573, whilst NSCLC A549 cells were barely affected. The combination of phenotypic assays, including wound healing, clonogenic and continuous live cell imaging provided a deeper understanding of the compounds’ mode of action. In particular, the latter demonstrated that isatin derivatives were able to induce necroptosis in SW1573 cells. The kinetics of cell death showed that necroptosis appeared after 2.5 h of exposure, which could be delayed to 7 h when co-treated with necrostatin-1. Interaction between the isatin derivatives and the KRAS G12C protein variant was discarded after in silico studies. Further studies are warranted to identify the cellular target responsible for the observed selectivity among cell lines.